Folk songs with short stories which are told related to Karaca Oglan - Simsek, Esma (Milli Folklor Dergisi, 2007)
It is still obvious that there are too many unknowns about the life of the famous minstrel, Karaca Oglan in the region of Cukurova. His poems were the main subject of the common talks and had come up to now. There had been a lot of beliefs, myths and stories related to Karaca Oglan among people. In this article, we will tackle on the stories about Karaca Oglan. We can classify Karaca Oglan's poems and stories under three main topics, such as; 1. Great Folk Stories: Karaca Oglan and Ismikan Sultan and Karaca Oglan stories. In one part of the story Han/Hal/Nar Malmut, Karaca Oglan is acted as a protector. 2. Printed Stories: The stories which were afterwards written by some authors according to Karaca Oglan's poems. Such as, Karaca Oglan and Spotted Girl, Karaca Oglan and Plateou beauty, Karaca Oglan and Karaca Kiz, Karaca Oglan and Bride Elif and Karaca Oglan's Love Adventures. 3. Folk Songs With Stories: Short stories which were formed in accordance with one or more folk songs. They are called Serkuste or Kaside in the East Anatolian region and Bozlak in the South Anatolia. There are also some folk songs about the adventures of Karaca Oglan. In our article, the stories in the third group are going to be handled in various cases.
Keywords: poet; Karaca Oglan; poetry; folk songs with stories